“Diagnóstico del Clima Organizacional en el Gobierno Autónomo Descentralizado Municipal del Cantón Chaguarpamba de la Provincia de Loja, periodo 2022-2023” - Guarnizo Solano de la Sala, Gabriela Alexandra (2025)
In public entities, organizational climate is a key determinant of continuous improvement and optimal institutional development. Evaluating it helps to provide feedback for any processes that directly affect it. Thus, the primary objective of this study was to assess the organizational climate in the Municipal Decentralized Autonomous Government (GAD) of Chaguarpamba canton during the period 2022-2023. This study included the following specific objectives: determining the level of organizational climate in the municipal GAD of Chaguarpamba, identifying the factors influencing organizational climate, and presenting a report with the results to the highest authority in the municipality. The methodology employed to achieve these objectives combined quantitative and qualitative data in a systematic manner. Due to the objective of obtaining information in its natural setting, the design was non-experimental. In this study, the phenomenon was analyzed theoretically and adapted to the study's reality. As a result of the deductive and analytical methods applied, the obtained information was organized to facilitate the extraction of relevant information, ranging from general aspects to specific details pertaining to the factors influencing whether an organization has a good or a bad organizational climate. A total of 66 public servants were interviewed and surveyed, with the instruments being based on the dimensions established by Litwin and Stringer. It was determined that the GAD has a very good organizational climate; however, there are factors that can be improved to foster greater institutional development. To ensure the highest authority and management have a clear understanding of how to achieve an excellent organizational climate, the results were presented in an executive report.